Development of a web application to share hobbies activities - Antonio Sarasa (Institute of Advanced Engineering and Science, 2022)
The widespread use of the web as a form of interaction has influenced the way people socialize. In this sense, this phenomenon has favored the development of web applications that offer user services aimed at sharing certain personal aspects such as photos, videos, or music. In particular, there is a growing demand for applications that allow users to search for other people who share the same hobbies intending to establish friendly relationships. The architecture for developing an application of this type is generally complex since it requires the manipulation of varied data, the storage of large amounts of data, or the possibility of communication between users in the application. This article presents an example of the design and development of a web application aimed at sharing activities among users who have common hobbies. For this, an ecosystem of different heterogeneous technologies has been used in a multilayer architecture, to optimize the management of the application information.